Melatonin enhances stem strength by increasing lignin content and secondary cell wall thickness in herbaceous peony. (18th April 2022) - Zhao, Daqiu; Luan, Yuting; Shi, Wenbo; Tang, Yuhan; Huang, Xingqi; Tao, Jun
Abstract: Cut flower quality is severely restrained by stem bending due to low stem strength. Melatonin has been shown to function in many aspects of plant growth and development, yet whether it can enhance stem strength, and the corresponding underlying mechanisms remain unclear. We investigated the role of melatonin in enhancement of stem strength in herbaceous peony ( Paeonia lactiflora Pall.) by applying exogenous melatonin and changing endogenous melatonin biosynthesis. Endogenous melatonin content positively correlated with lignin content and stem strength in various P. lactiflora cultivars. Supplementation with exogenous melatonin significantly enhanced stem strength by increasing lignin content and the S/G lignin compositional ratio, up-regulating lignin biosynthetic gene expression. Moreover, overexpression of TRYPTOPHAN DECARBOXYLASE GENE ( TDC ) responsible for the first committed step of melatonin biosynthesis in tobacco, significantly increased endogenous melatonin, which further increased the S/G ratio and stem strength. In contrast, silencing PlTDC in P. lactiflora decreased endogenous melatonin, the S/G ratio and stem strength. Finally, manipulating the expression of CAFFEIC ACID O-METHYLTRANSFERASE GENE ( COMT1 ), which is involved in both melatonin and lignin biosynthesis, showed even greater effects on melatonin, the S/G ratio and stem strength. Our results suggest that melatonin has a positive regulatory effect on P. lactiflora stem strength. Abstract : Exogenous and endogenous melatonin increases plant stem strength by increasing lignin accumulation (particularly S-lignin) and secondary cell wall thickness.